2019
DOI: 10.1523/eneuro.0318-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation in Adolescence Disrupts Cortical Development and Goal-Dependent Decision-Making in Adulthood, Despite Social Reintegration

Abstract: The social environment influences neurodevelopment. Investigations using rodents to study this phenomenon commonly isolate subjects, then assess neurobehavioral consequences while animals are still isolated. This approach precludes one from dissociating the effects of on-going versus prior isolation, hindering our complete understanding of the consequences of social experience during particular developmental periods. Here, we socially isolated adolescent mice from postnatal day (P)31 to P60, then re-housed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 72 publications
2
48
1
Order By: Relevance
“…These changes also increase vulnerability to the development of long-lasting psychiatric disorders, particularly following perturbations that may disrupt brain development occurring during adolescence. For example, preclinical studies find that stress (such as social isolation) or drug use in adolescence can alter decision making, impair cognition, and increase drug use in adulthood, even when stress or drug use are constrained to adolescence (Butler et al, 2016;Spear, 2016;DePoy et al, 2017;Hinton et al, 2019). This study gives us novel insight into age-related differences in dopamine release and its regulation.…”
Section: Discussionmentioning
confidence: 94%
“…These changes also increase vulnerability to the development of long-lasting psychiatric disorders, particularly following perturbations that may disrupt brain development occurring during adolescence. For example, preclinical studies find that stress (such as social isolation) or drug use in adolescence can alter decision making, impair cognition, and increase drug use in adulthood, even when stress or drug use are constrained to adolescence (Butler et al, 2016;Spear, 2016;DePoy et al, 2017;Hinton et al, 2019). This study gives us novel insight into age-related differences in dopamine release and its regulation.…”
Section: Discussionmentioning
confidence: 94%
“…Our study adds to a growing body of research demonstrating that spine density and dynamics change within agranular frontal cortices during adolescence (Zuo et al, 2005;Gourley et al, 2012;Johnson et al, 2016;Boivin et al, 2018), and provides novel evidence that spine pruning onto a projection-defined cell-type in the frontal cortex is sensitive to pubertal development. More work needs to be done in order to understand how spine pruning relates to changes in neural computation and cognitive processes during adolescence (Selemon, 2013), but recent studies have made progress, associating changes in spine density onto OFC neurons to alterations in goal-directed behavior (DePoy et al, 2019;Hinton et al, 2019). Data in humans suggests that pubertal status and circulating gonadal hormone levels influence working memory use during learning in both sexes (Master et al, 2019), sensitivity to immediate rewards during intertemporal decision-making in males (Laube et al, 2017), and a variety of social and affective behaviors in both sexes (Vijayakumar et al, 2018;Goddings et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…FSP is a dramatic process of brain circuit remodeling in which some dendritic spines and synapses are stabilized and refined, while others (up to 50% in some frontocortical regions) are pruned (see ref. [15]). Adolescent FSP is associated with the emergence of goal‐oriented social and sexual behavior and cognition, including mastery of stressful challenges of ordinary life recognized as triggers for SZ onset by Bleuler decades ago, [ 16 ] such as leaving home, establishing independent quarters, finding and holding employment, engaging in courtship and marriage, joining the military, and creating a family.…”
Section: What Does the Association Of Schizophrenia With Synaptic Prumentioning
confidence: 99%
“…Adolescence is a critical period during which social experience optimizes one's ability to seek and attain goals later in life, and age‐typical dendritic spine elimination is an essential feature of this maturational phase, in the absence of which social mammals tend to defer to regressive behaviors that appear maladaptive or even psychotic, as argued by Hinton et al. [ 15 ] Hinton et al. [ 15 ] showed that FSP is delayed and diminished in weaned mice that are removed from a same‐sex peer group and placed in social isolation for the duration of adolescence.…”
Section: Concentration On Molecular Pharmacology Ignores Evolutionarymentioning
confidence: 99%
See 1 more Smart Citation